Antiepileptic drugs prescription utilization behavior and direct costs of treatment in a national hospital of India - Haroon, Ahsan (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND AND OBJECTIVES: The present study evaluated the direct costs of active epilepsy and looked at the pattern of drug prescription and utilization in epileptic patients visiting the neuroscience centre of a national hospital of India. MATERIALS AND METHODS: A total of 134 epileptic patients were studied over a period of 4 months. Patients demography, commonly prescribed antiepileptic drugs (AEDs), socioeconomic status, direct costs, response ratio (RR) for newer drugs, and quality of life (QOLIE-10) was evaluated. RESULTS AND DISCUSSION: We found a higher percentage of male patients (67.9%) as compared with females. Most of the patients were in the age group 11–30 years and majority of them (39.6%) belonged to lower middle group. A higher percentage (68.7) of drugs was prescribed as polytherapy. Higher monthly cost was observed for some of the newer AEDs including the lamotrigine, levetiracetam, and lacosamide as compared with older drugs. Among the newer drugs, clobazam had the lowest cost. RR was calculated for 12 patients out of which 8 had a RR < –0.50. The QOL domains, following conventional or newer drugs, were not much affected. CONCLUSION: The study indicates an increasing trend toward clinical usage of newer AEDs, increasing trend of poly-therapy with significant escalations in the cost of therapy.